KEDISIPLINAN DAN IKLIM SEKOLAH UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA (PENELITIAN DI MI CIPEUSAR KOTA TASIKMALAYA) - Nugraha, Doni (Manajerial | Journal Manajemen pendidikan islam, 2024)
The purpose of this study was to analyze the discipline and school climate on the learning performance of students at MI Cipeusar Tasikmalaya City. The method used is descriptive qualitative. the results of this study indicate that the magnitude of the influence of discipline and school climate on student learning achievement together is 57.4%. While the remaining 42.6% of students' learning achievement is determined by other variables besides discipline and school climate that are not examined in this study. Referring to the results of this study where it is known that student discipline and school climate affect student learning achievement, it is necessary for students, teachers, principals and student guardians to pay attention to this so that the teaching and learning process can obtain satisfactory results.